BURNOUT AMONG NURSES WORKING IN NATIONAL INSTITUTE OF MENTAL HEALTH, SRI LANKA (Proceedings of the International Conference on Public Health, 2022)
In many countries’ majority of the national health workforce is made up ofnurses thus they play a major role in health care delivery. Burnout is a physical orpsychological fatigue or exhaustion felt by an individual due to personal, work and clientrelated stressors. Previous studies report that nurses, especially psychiatric nurses are moreprone to burnout which may adversely affect service delivery. Objective of the study wasto determine the level of burnout among psychiatric nurses in National Institute of MentalHealth Sri Lanka. A descriptive cross-sectional study was conducted among all nursesinvolved in patient care (n=346) working at National Institute of Mental Health, Sri Lanka.The study instrument was a self-administered questionnaire. Burnout was measured usingthe translated and validated Copenhagen Burnout Inventory (CBI). Cut off value of overallburnout was taken as 40.16 points according to the validation study. Response rate was85%(n=296). Prevalence of burnout was 31.8% (95% CI of 30.5% - 33.55%). Adjustedprevalence was 27.1% when considering the Positive predictive value/sensitivity of CBI.Highest mean score was seen in Personal burnout which was 40.75(+18.76 SD) with a95% CI of 38.60-42.90. Work related burnout had a mean score of 29.24(+17.76SD) witha 95% CI of 27.22-31.28. Client related burnout was 29.53(+16.97SD) with a confidenceinterval of 27.59-31.47. Total burnout score was 33.25 (+of 15 SD) with a confidenceinterval of 31.53-34.96. In conclusion, Burnout affects more than one third of nurses atNIMH. Personal burnout score was significantly higher than the means of work related orclient related burnout scores. It is a responsibility of health managers to address thisproblem before it compromises patient care at NIMH.
Keywords: psychiatric nurses, burnout, prevalence